Modernitas dan Tantangan Perkembangan Pemikiran Islam di Indonesia - Mahfud, Mahfud (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Modernity is an inevitable reality and part of the natural order (sunnatullah) that must be accepted and addressed by every society, including the Muslim community. This article examines the response of Islamic thought to the challenges of modernity, particularly in the context of Indonesia. It argues that Islam, as both a religion and a cultural system, offers its own framework for engaging with modern developments. Various Islamic thinkers have contributed significantly to shaping this discourse. Prominent figures from the Middle East such as Sayyid Qutb, Hasan al-Banna, Khomeini, Nasr Hamid Abu Zayd, Mohammed Arkoun, and Hassan Hanafi have influenced global Islamic thought. In Indonesia, the development of Islamic ideas in response to modernity is reflected in the works of intellectuals such as Nurcholish Madjid, Abdurrahman Wahid (Gus Dur), and Ulil Abshar Abdalla. This paper focuses on the evolution of Islamic liberalism in Indonesia as a contextual response to modernity, highlighting how local Islamic thought seeks to reconcile faith with contemporary realities.